Pengaruh Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Pada PT. Indo Lampung Perkasa - Yoeyong Rahsel; Septiana Mar’atus Sholikhah (Jurnal Manajemen DIVERSIFIKASI, 2025)
In essence, each person's level of job satisfaction is unique. The system and values that are relevant toeach employee will determine the varying degrees of pleasure that they experience. The test resultsindicate that there is a relationship between organizational culture and job satisfaction at PT. IndoLampung Perkasa. This relationship is further supported by respondents' responses, which highlightthe following: superiors always communicate to subordinates about efforts to complete tasks;employees who work well at PT. Indo Lampung Perkasa are fairly given opportunities to getpromoted; employees who take risks and dare to try new things are all highly initiative in carryingout their work. This study's goal was to ascertain the impact of organizational culture, which in thisinstance is thought to be responsible for employee contentment. Multiple linear regression analysis isthe technique employed. The study's findings indicate that there is a relationship between employeesatisfaction and company culture.